О чем не пишет ДостоевскийWhat Dostoevsky did not write about - Egeberg, Erik (Poljarnyj vestnik, 2013)
Unsurprisingly, most scholarship on Dostoevsky concerns what Dostoevsky explicitly wrote about - first and foremost the religious, philosophical, and psychological questions emerging from his texts. The present article, on the contrary, addresses what Dostoevsky did not include in his novels, with special focus on information lacunae in Demons.